Act of March, 1886 (Published as “Notice”), ST. MARY’S BEACON, Oct. 13, 1887 at 2. (Leonard Town, MD) - (:unkn) unknown (General Publisher, 1886)
Prohibited carry on days of elections, within three hundred yards of the polls, any gun, pistol, dirk, dirk-knife, razor, billy, or bludgeon in St. Mary's County. Any constable who shall refuse to arrest any person violating the provisions shall be deemed guilty of a misdemeanor, fined not less than fifty nor more than one hundred dollars.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES